Estudio de la actividad antioxidante y antimicrobiana del aceite esencial de las hojas de Piper Pubinervulum C. DC Proveniente de Macas, Ecuador. - Abad Dávila, Juan Camilo (2014)
The following investigation determinate the activity antioxidant of essential oil of leaves of Piper pubinervulum which comes from the city Macas, Ecuador. Using methods of free radical inhibition DPPH y ABTS can obtain a IC50 equal to 20,399 μg / mL y 0,416 μg / mL as result, at the moment of compare with IC50 the oils of Thymus vulgaris with 0,414 μg / mL y 0,231 μg / mL, shows an antioxidant activity less than the oil in study. Using the fotoquimioluminiscencia method with an antioxidant capacity of 1,8 μmol Trolox / g. It was also determined antimicrobial activity by the agar diffusion with disks method. Between the batteries in the assay, Escherichia coli ATCC* 8739™ y Staphylococcus aureus subsp. Aureus ATCC* 6538P™ which was the most susceptible with a result of MIC of 6,08 y 3,09 mg / mL between of the assay yeast, Candida albicans ATCC 10231™ was the most susceptible showing a MIC of 0,3909 mg / mL.